Correction: Efficient polymer light-emitting diodes (PLEDs) based on chiral [Pt(C^N)(N^O)] complexes with near-infrared (NIR) luminescence and circularly polarized (CP) light. Issue 2 (13th December 2019) - Fu, Guorui; He, Yani; Li, Wentao; Wang, Baowen; Lü, Xingqiang; He, Hongshan; Wong, Wai-Yeung
Abstract : Correction for 'Efficient polymer light-emitting diodes (PLEDs) based on chiral [Pt(C^N)(N^O)] complexes with near-infrared (NIR) luminescence and circularly polarized (CP) light' by Guorui Fu et al., J. Mater. Chem. C, 2019, 7, 13743–13747.